Influencer Culture dalam Pembentukan Budaya Konsumtif dan Hiperrealitas Gen Z (Studi Pada Akun Tiktok @tasyafarasya) - Pratami, Rezki; Estriana, Virna (Jurnal Sosial Teknologi, 2025)
The rapid development of social media in the digital era has influenced the communication patterns and consumer behavior of Generation Z, especially through the influencer culture phenomenon on TikTok. Generation Z, as the dominant TikTok users in Indonesia, uses influencer content as a lifestyle reference and digital status symbol. This study aims to answer two main research questions: (1) how influencer culture on TikTok shapes Gen Z's consumer behavior, and (2) how the concept of hyperreality emerges in Gen Z's interactions with influencer content. The theoretical study uses the parasocial communication framework (Horton & Wohl, 1956), Baudrillard's hyperreality theory (1983), semiotics (Eryanto, 2013), and Fairclough's critical discourse analysis (1995). This research method is qualitative with a case study approach on the TikTok account @tasyafarasya. Data were collected through content observation, comment analysis (likes, engagement), as well as references to academic literature and recent social media reports. The results show that personal narratives, haul videos, and live shopping on the @tasyafarasya account build parasocial relationships that foster pseudo-emotional closeness. This content, rich in symbols and visual signs, creates a simulation of idealized images that distort reality, so that products serve as status symbols rather than merely practical functions. The study's conclusions confirm that influencer culture on TikTok is not simply a marketing strategy, but a space for the production of symbolic meaning that shapes Gen Z's identity and consumer behavior in the era of digital hyperreality